Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - Siegel, David A.; Buesseler, Ken O.; Behrenfeld, Michael J.; Benitez-Nelson, Claudia R.; Boss, Emmanuel; Brzezinski, Mark A.; Burd, Adrian; Carlson, Craig A.; D'Asaro, Eric A.; Doney, Scott C.; Perry, Mary J.; Stanley, Rachel H. R.; et al. (Frontiers in Marine Science, 2016)
Ocean ecosystems play a critical role in the Earth’s carbon cycle and the quantification of their impacts for both present conditions and for predictions into the future remains one of the greatest challenges in oceanography. The goal of the EXport Processes in the Ocean from Remote Sensing (EXPORTS) Science Plan is to develop a predictive understanding of the export and fate of global ocean net primary production (NPP) and its implications for present and future climates. The achievement of this goal requires a quantification of the mechanisms that control the export of carbon from the euphotic zone as well as its fate in the underlying “twilight zone” where some fraction of exported carbon will be sequestered in the ocean’s interior on time scales of months to millennia. Here we present a measurement / synthesis / modeling framework aimed at quantifying the fates of upper ocean NPP and its impacts on the global carbon cycle based upon the EXPORTS Science Plan. The proposed approach will diagnose relationships among the ecological, biogeochemical and physical oceanographic processes that control carbon cycling across a range of ecosystem and carbon cycling states leading to advances in satellite diagnostic and numerical prognostic models. To collect these data, a combination of ship and robotic field sampling, satellite remote sensing and numerical modeling is proposed which enables the sampling of the many pathways of NPP export and fates. This coordinated, process-oriented approach has the potential to foster new insights on ocean carbon cycling that maximizes its societal relevance through the achievement of research goals of many international research agencies and will be a key step towards our understanding of the Earth as an integrated system.